Perineal massage in labour and prevention of perineal trauma: randomised controlled trial - Stamp, Georgina (BMJ, 2001)
OBJECTIVE: To determine the effects of perineal massage in the second stage of labour on perineal outcomes. DESIGN: Randomised controlled trial. PARTICIPANTS: At 36 weeks' gestation, women expecting normal birth of a singleton were asked to join the study. Women became eligible to be randomised in labour if they progressed to full dilatation of the cervix or 8 cm or more if nulliparous or 5 cm or more if multiparous. 1340 were randomised into the trial. INTERVENTION: Massage and stretching of the perineum during the second stage of labour with a water soluble lubricant. MAIN OUTCOME MEASURES: Primary outcomes: rates of intact perineum, episiotomies, and first, second, third, and fourth degree tears. Secondary outcomes: pain at three and 10 days postpartum and pain, dyspareunia, resumption of sexual intercourse, and urinary and faecal incontinence and urgency three months postpartum. RESULTS: Rates of intact perineums, first and second degree tears, and episiotomies were similar in the massage and the control groups. There were fewer third degree tears in the massage group (12 (1.7%) v 23 (3.6%); absolute risk 2.11, relative risk 0.45; 95% confidence interval 0.23 to 0.93, P<0.04), though the trial was underpowered to measure this rarer outcome. Groups did not differ in any of the secondary outcomes at the three assessment points. CONCLUSIONS: The practice of perineal massage in labour does not increase the likelihood of an intact perineum or reduce the risk of pain, dyspareunia, or urinary and faecal problems.